Identification of rare sequence variation underlying heritable pulmonary arterial hypertension - Stefan Gräf (Nature Portfolio, 2018)
Pulmonary arterial hypertension (PAH) is a rare lung disorder characterised by narrowing and obliteration of small pulmonary arteries ultimately leading to right heart failure. Here, the authors sequence whole genomes of over 1000 PAH patients and identify likely causal variants in GDF2, ATP13A3, AQP1 and SOX17.